Հակաուտոպիան որպես ապագայի կանխորոշման միջոց - Մերի Միքայելյան (ՀՀ ԳԱԱ հրատ.)
В этой статье антиутопия представляется как социокультурное явление, нацеленное на предсказание будущего. Антиутопия это критика утопии с точки зрения стремления к утопическому идеалу и достижения совершенства.This article depicts dystopia as a sociocultural phenomenon, extrapolating the future or foreseeing it. Dystopia is a denouncement of utopia from the point of striving towards the ideal and attaining perfection.
Keywords: Philosophy; Psychology; Religion